PEMBUATAN APLIKASI IMANUELCIO EXPRESS JASA PENGIRIMAN KARGO EKSPEDISI BERBASIS WEBSITE - Rani Puspita; Rina Astriani (Asosiasi Dosen Muda Indonesia, 2024)
This research was related to the design and development of website-based applications for delivery and goods tracking services. The main objective of this research is to created a web-based application that makes it easier for customers and companies to send goods and track goods. Because in the goods delivery process customers cannot find out information about ordering their goods, this research focuses on creating the iManuelcio Express Application for Website-based Expedition Cargo Delivery Services. The research method used SDLC, starting from design to the implementation stage. Development Results This application was successfully built according to the objectives and can be used on desktops and smartphones. This website can be accessed at the URL https://carmudi.dev:8080/ .